THE PERSPECTIVE OF SLA PRINCIPLES OF MATERIALS ANALYSIS ON A THEMATIC ENGLISH TEXTBOOK FOR SIXTH-GRADE ELEMENTARY SCHOOL - Camalia Fatih Nida (Universitas Bengkulu, 2021)
This study attempts to explain the materials of the thematic English textbook entitled “Grow with English” for sixth grade by reflecting the SLA principles. Therefore, it could be useful as a preliminary step before conducting a textbook evaluation. This article used a qualitative research method with the focus of content analysis. The writer derived the results by responding to the materials analysis proposed by Littlejohn (2011) regarding three main questions (1) what is the learner expected to do?, (2) who with? and (3) with what content?. Each question depicted certain criteria that elaborate the elements of those three questions to outline coursebook materials. Moreover, to complete the analytical of textbook task-based analysis, the writer used the concept of ten SLA principles as suggested by Ellis (2005). The results showed that game-based tasks and consciousness-raising tasks are effective in supporting L2 acquisition since they derived both explicit and implicit knowledge. This study is limited on the scope that only focuses on a preliminary stage before conducting an in-use evaluation. The findings of this study could be a consideration and reference for EFL teachers, creators of English coursebook materials, and English coursebook policymakers, especially in Indonesia to put more attention on the importance of SLA principles in the textbook’s materials that can support students’ L2 acquisition.